Gilles Deleuze and the “truth of truth”: thinking about forces - Romero Pardo, Alejandro (Logos. Anales del Seminario de Metafísica, 2022)
In this paper, we will study Gilles Deleuze's conception of truth, in its close connection with the real forces that produce thought. First, we will trace some keys to Deleuze's critique of representation, focusing on his reading of Platonic philosophy and his opposition to the "dogmatic image of thought". The representational way of thinking derives from a certain conception of truth, which Deleuze radically opposes. As we shall see, it is not a question of denying the true, but of linking it to a "truth of truth" which determines its value according to the multiple forces of thought. By way of conclusion, three senses will be distinguished in Deleuze's notion of truth, and the sufficiency of the criteria proposed by his thought to distinguish between the forces and forms of life that lie behind all truth will be questioned.
Keywords: Representation; dogmatic image of thought; foundation; truth; forces; way of life; plurality